Lexicographical Analysis of Russian and Armenian Synonymous Series with the Semantic Component ‘High’ - Grdzelyan, Rouzan (Bulletin of Yerevan University H: Russian Philology, 2024)
The article is devoted to a comparative typological analysis of synonymous series with the semantic component ‘high’ in the Russian and Armenian languages. Such an analysis helps to identify deep meaning-generating processes that influence the semantic organization of synonymous series, as well as to describe the linguocultural and lexico-typological features of two Indo-European languages ​​- Russian and Armenian. Research methods such as lexicographic analysis of synonymous series and application of dictionary entries of dominant lexemes make it possible to identify semantic components and semantic nodes in the structure of the lexical meaning of the group of words under study. Identification and description of such features of lexemes can become a starting point in further research into the lexical-typological and linguistic-cultural characteristics of the two languages. As a result of our lexicographic analysis of Russian and Armenian synonymic series with the semantic component ‘high’, we came to the following conclusions: 1. These series differ in the degree of synonymous variability: Armenian synonymous series are distinguished by greater variability. 2. The degree of variability is manifested in the length of the synonymous series: their approximate ratio is 15 lexemes in Russian, 70 lexemes in Armenian. 3. The degree of variability also affects the semantic asymmetry of the semantic organization of the synonymous series: in the Armenian language there are more semantic nodes, therefore, more semantic components.